Neural computing for advanced applications : first international conference, NCAA 2020, Shenzhen, China, July 3-5, 2020, Proceedings /: first international conference, NCAA 2020, Shenzhen, China, July 3-5, 2020, Proceedings. ([2020]) - Unknown
No abstract available